Lamotheoxyuris ackerti n. gen., n. comb. (Nematoda: Heteroxynematidae) parasite of Neotoma spp. (Rodentia: Muridae) Lamotheoxyuris ackerti n. gen., n. comb. (Nematoda: Heteroxynematidae) parásito de Neotoma spp. (Rodentia: Muridae) - JORGE FALCÓN-ORDAZ; JESÚS A FERNÁNDEZ; LUIS GARCÍA-PRIETO (Revista Chilena de Historia Natural, 2010)
On the basis of the revision of the type material of Aspiculuris ackerti Kruidenier & Mehra, 1959, and new specimens collected from Neotoma nelsoni Goldman, 1905 (Rodentia: Cricetidae), in Veracruz, Mexico, we herein to which A. ackerti is transferred as Lamotheoxyuris ackerti This new genus differs from all other genera included in 1) mouth surrounded by six lips; 2) extension of lateral alae describe a new genus (Lamotheoxyuris n. gen.), (Kruidener & Mehra, 1959) n. gen., n. comb. Heteroxynematinae by the following main traits: reduced; and 3) lack of caudal alae. Con base en la revisión del material tipo de Aspiculuris ackerti Kruidenier y Mehra, 1959 y de nuevos ejemplares recolectados en Neotoma nelsoni Goldman, 1905 (Rodentia: Cricetidae), en Veracruz, México, se describe un nuevo género (Lamotheoxyuris n. gen.), al que A. ackerti es transferido como Lamotheoxyuris ackerti (Kruidener y Mehra, 1959) n. gen., n. comb. Este nuevo género se distingue de todos los demás géneros incluidos en Heteroxynematinae por las siguientes características: 1) presencia de seis labios rodeando la boca; 2) extensión reducida del ala lateral; y 3) carencia de ala caudal.